Variability of the structure and directions in the development of heaths and psammophilous grasslands within the artillery range near the city of Toruń - Chojnacka, Joanna; Cyzman, Wiesław; Nienartowicz, Andrzej; Deptuła, Miłosz (Ecological Questions, 2010)
Phytosociological analysis of non-forest communities was carried out on one of the oldest and the biggest military training grounds in Europe, located near the city of Toruń, in central Poland. Heaths and psammophilous grasslands developed here as a result of deforestation of inland dunes in the valley of the Vistula River, as well as a result of destruction of soils and vegetation brought on by manoeuvres and artillery firings. They form a landscape mosaic with young self-seeding pines, mature pine forests and birch forests. Using the Braun-Blanquet method, 84 relevés were made in the areas dominated by dwarf shrubs and 32 relevés within psammophilous grasslands. Applying the classic phytosociological method, the following plant associations were distinguished in the first set of relevés: Pohlio-Callunetum and Arctostaphylo-Callunetum, as well as the community with Cytisus scoparius. Within the psammophilous grasslands, two associations were distinguished: Spergulo vernalis-Corynephoretum and Calamagrostietum epigeji. In this paper, the heterogeneity within associations and communities was presented together with descriptions of individual syntaxa, as well as dynamic and developmental relationships between the aforementioned were identified.